Penerapan Antisipasi Perundungan (Bullying) pada Sekolah Dasar di Kota Tenggarong - Nursasari, Nursasari (Program Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2017)
Perundungan at school is another form of the oppressive action against peer student whom perceived as weak, in some case, may cause a traumatic impact. By the early consciousness of its negative impact has triggered the SDIT Nurul Ilmi, SDN 002 and SDN 028 establishes policy of the Perundungan Anticipative Program. This research is meant to find out body of program and its implementation, as well as, the obstacle and supporting factor of the Perundungan Anticipative Program at SDIT Nurul Ilmi, SDN 002 and SDN 028. Method used in the research is qualitative with a qualitative-descriptive approach. The results of this study illustrate the form of anticipatory perundungan programs in the three schools are CCTV, polgu, polkam, no tech bench, committee, polkam, welcome students, murojah morning, dhuha prayer, tilawati, zippy's friend, ekstakulikuler, business day, visit and mushraka. The research result describes two forms of the perundungan anticipative applications, id est : 1) The Precautionary-measure, this is shown by the provision of the cutting-edged CCTV facilities, the teacher interim, the no-tech bench, committee, and security officer — who guards during break time. 2) The Prevention-measure, by the Character Building effort and the Religious Approach to student, through activities, such as, students’ inaugural, morning murojah, Dhuha Shalah, tilawati, zippy’s friend, extracurricular (boyscout, theater), business day, visitations, and musharaka. By all of the school residents’ support, and some ruled-out minors, the implementation of the perundungan anticipative program is declared as successful. And an absolute low rate of absenteeism has marked the successfulness of this program